Study protocol of a randomized controlled trial to test the effect of a smartphone application on oral-health behavior and oral hygiene in adolescents with fixed orthodontic appliances - Janneke F. M. Scheerman; Berno van Meijel; Pepijn van Empelen; Gem J. C. Kramer; Gijsbert H. W. Verrips; Amir H. Pakpour; Matheus C. T. Van den Braak; Cor van Loveren (BMC, 2018)
Abstract Background Adolescents with fixed orthodontic appliances are at high risk of developing dental caries. To date, new smartphone technologies have seldom been used to support them in the preventive behavior that can help prevent dental caries. After an intervention-mapping process, we developed a smartphone application (the WhiteTeeth app) for preventing dental caries through improved oral-health behavior and oral hygiene. The app, which is intended to be used at home, will help adolescents with fixed orthodontic appliances perform their oral self-care behavior. The app is based on the Health Action Process Approach (HAPA) theory, and incorporates several behavior-change techniques that target the psychosocial factors of oral-health behavior. This article describes the protocol of a randomized controlled trial (RCT) to evaluate the effects of the WhiteTeeth app on oral-health behavior and oral-hygiene outcomes (presence of dental plaque and gingival bleeding) compared with those of care as usual, in patients aged 12-16 with fixed orthodontic appliances. Methods/design The RCT has two conditions: an experimental group that will receive the WhiteTeeth app in addition to care as usual, and a control group that will only receive care as usual. Care as usual will include routine oral-health education and instruction at orthodontic check-ups. In the western part of the Netherlands 146 participants will be recruited from four orthodontic clinics. Data will be collected during three orthodontic check-ups: baseline (T0), 6 weeks of follow-up (T1) and 12 weeks of follow-up (T2). The primary study outcomes are the presence of dental plaque (measured with a modified Silness and Loë Plaque Index); and gingival bleeding (measured with the Bleeding on Marginal Probing Index). Secondary outcomes include changes in self-reported oral-health behaviors and its psychosocial factors identified by the HAPA theory, such as outcome expectancies, intention, action self-efficacy, coping planning and action control. Discussion Since the intervention was designed to target psychosocial factors in the motivational and volitional components of the behavior-change process, we hypothesize that the app will cause greater improvements in oral-health behavior and oral hygiene more than traditional oral-health-promotion programs (i.e., care as usual). Trial registration. The trial has been registered with the Dutch Trial Register (NTR6206: 20 February 2017).